Investigation of the structural properties of polyamide nanofiltration membrane - Wallace, Edwin; Cuhorka, Jiří; Mikulášek, Petr (Česká membránová platforma (CZEMP), 2016)
In this present work, a polyamide thin-film composite NF membrane (AFC 30) was used for characterization of the structural properties. The interpretation of values from the different uncharged solutes rejection allows determining the structural properties of AFC 30. This was done by using modelling of rejection of the uncharged solutes with the help of the Donnan steric partitioning model (DSPM). In addition, the membrane was considered to be modelled as bundle of cylindrical pores. It was observed that the pore radius and thickness to porosity from AFC 30 membrane are similar irrespective of the different uncharged solutes. The results confirm that experimental rejection and calculated rejection using the average value of pore size (0.51 nm) and thickness to porosity (2.23 nm) were in good agreement which reveals that AFC 30 is a loose NF membrane.
Zkoumání strukturálních vlastností polyamidových nanofiltračních membrán
Keywords: nanofiltration; polyamide membrane; characterization; DSPM model; nanofiltrace; polyamidová membrána; charakterizace; DSPM model